SISTEM PENGANGGARAN PENDIDIKAN TINGGI DARI OLD PUBLIC MANAGEMENT MENUJU NEW PUBLIC MANAGEMENT - A. Budi Santosa (Institut Agama Islam Negeri Purwokerto, 2014)
Budget implementation in government agencies has not been effective even though legislation has mandated that performance-based budgeting should be implemented gradually starting in 2005. Some researches on budgeting found a disregard for the prerequisites for the successful implementation of performance-based budgeting, which includes participation, competence, and the clear documents and budgeting procedures. In Indonesia, the reform of budgeting begins with the issuance of Act No. 17 of 2003 on State Finance and Act No. 25 of 2004 on National Development Planning System, which is a product of legislation that became a milestone of reform in national planning and budgeting. In universities in Indonesia budget management system changes begins to be applied especially after the implementation of autonomy in the management of higher education institutions, namely since the issuance of Government Regulation on Higher Education as State-Owned Legal Entity (BHMN), Public Service Agency (BLU), even the latter leads to the State University-Owned Legal Entity(PTN-BH). The change of financial management is not without reason, but is intended to more financial management of performance-oriented, transparent and accountable, the estuary of the increasing good governance.Â Pelaksanaan anggaran di instansi pemerintah selama ini belum efektif, padahal undang-undang telah mengamanatkan bahwa pelaksanaan penganggaran berbasis kinerja hendaknya dapat dilaksanakan secara bertahap mulai tahun 2005. Beberapa hasil penelitian tentang penganggaran menunjukan adanya pengabaian terhadap prasayarat keberhasilan pelaksanaan penganggaran berbasis kinerja, yang antara lain ditentukan oleh faktor-faktor pendukung seperti partisipasi, kompetensi, dan adanya kelengkapan dokumen dan prosedur penganggaran secara jelas. Di Indonesia, reformasi bidang penganggaran diawali dengan terbitnya Undang-undang Nomor 17 Tahun 2003 tentang Keuangan Negara Undangundang Nomor 25 Tahun 2004 tentang Sistem Perencanaan Pembangunan Nasional merupakan produk undang-undang yang menjadi tonggak sejarah reformasi di bidang perencanaan dan penganggaran nasional. Di lingkungan perguruan tinggi Indonesia perubahan sistem manajemen anggaran mulai diterapkan terutama setelah dilaksanakannya otonomi dalam pengelolaan lembaga pendidikan tinggi, yaitu sejak diterbitkannya Peraturan Pemerintah tentang Perguruan Tinggi sebagai BHMN, BLU, bahkan yang terakhir ini mengarah pada PTN-BH. Perubahan arah pengelolaan keuangan tersebut tidak tanpa alasan, namun dimaksudkan agar pengeloaan keuangan lebih berorientasi pada kinerja, transparan dan akuntabel, yang muaranya tentu pada meningkatnya good governance.